Dual enhancement of light extraction efficiency of flip-chip light-emitting diodes with multiple beveled SiC surface and porous ZnO nanoparticle layer coating. (13th April 2015) - Mao, Peng; Xu, Mingsheng; Chen, Jing; Xie, Bo; Song, Fengqi; Han, Min; Wang, Guanghou
Abstract: A porous ZnO nanoparticle layer coating composed of columnar ZnO nanoparticle piles and a multiple-beveled substrate was used to enhance the light extraction efficiency of GaN-based flip-chip light-emitting diodes (FC-LEDs), which were grown on high-purity SiC substrates. The SiC substrate was multiple-beveled by fabricating an 'X' pattern on the face of it, followed by a deposition of a porous ZnO nanoparticle layer on the 'X'-patterned surface. A porous ZnO nanoparticle layer was fabricated with gas phase cluster beam deposition in a glancing incidence. The incident angular-resolved light transmission of the ZnO nanostructure beyond the critical angle of total internal reflection (TIR) was greatly enhanced. The light output power of the LED was improved by nearly 60% compared to the original planar GaN-based LED on an SiC substrate (FC-SLED), which contained a significant enhancement supplemental to the 18% electroluminescence (EL) enhancement realized with the 'X'-pattern beveling. We demonstrated that a dual enhancement of light extraction efficiency was achieved by using the hierarchical surface consisting of microscale textures (the multiple-beveled surfaces) and nanoscale structures (the ZnO nanoparticle layers).